Service Quality, Corporate Image, and Customer Trust: Revealing Interconnected Dynamics among Hotel Customers - Yusuf, Hayat; Roslan, Astil Harli (PT. Riset Press International, 2024)
This research aims to examine the relationship between service quality, corporate image, and customer trust using a quantitative method with a cross-sectional design and PLS 4 data analysis based on a survey of 121 hotel customers in Kendari, Indonesia. The findings indicate that customer trust has a significant positive impact on corporate image, and statistically, an increase in customer trust enhances the corporate image. Service quality also has a significant positive effect on both corporate image and customer trust, with partial mediation by customer trust. The practical implications suggest that hotel companies should focus on improving customer trust and service quality to strengthen their corporate image. The study's limitations include data solely from the hospitality sector and a cross-sectional design that restricts the assessment of causal relationships. Future research is recommended to expand the scope to other industry sectors, employ a longitudinal design, and explore additional variables such as customer satisfaction and loyalty, as well as qualitative methods for deeper insights.